2007
DOI: 10.2165/00128071-200708020-00004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Cyclophosphamide, Azathioprine, and Cyclosporine (Ciclosporin) as Adjuvant Drugs in Pemphigus Vulgaris

Abstract: Oral prednisone with cyclophosphamide is the most effective treatment for pemphigus vulgaris. All therapy regimens had a similar safety profile. In our opinion, cyclophosphamide at a dose of 1.1-1.5 mg/kg/day should be the adjuvant drug of choice in the treatment of moderate-to-severe pemphigus vulgaris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 6 publications
1
36
0
3
Order By: Relevance
“…42 Measures to prevent bladder toxicity, other than minimising cumulative dose exposure, include avoiding night administration and therefore overnight bladder exposure to acrolein, forced diuresis with hyper-hydration and concurrent 2-mercaptoethanesulfonic acid (Mesna) to bind and inactivate acrolein. 37 Mesna has shown prophylactic efficacy in only some oncological trials, therefore the American Society of Clinical Oncology recommends use only with high cyclophosphamide doses (e.g.…”
Section: Haemorrhagic Cystitismentioning
confidence: 99%
“…42 Measures to prevent bladder toxicity, other than minimising cumulative dose exposure, include avoiding night administration and therefore overnight bladder exposure to acrolein, forced diuresis with hyper-hydration and concurrent 2-mercaptoethanesulfonic acid (Mesna) to bind and inactivate acrolein. 37 Mesna has shown prophylactic efficacy in only some oncological trials, therefore the American Society of Clinical Oncology recommends use only with high cyclophosphamide doses (e.g.…”
Section: Haemorrhagic Cystitismentioning
confidence: 99%
“…However, cyclophosphamide (1.1-1.5 mg/kg/day) combined with prednisone was found to be slightly more effective (the average time to clinical remission was 6.8 6 10.5 months, with the percentage of patients who remained clinically free of disease being 55%). 121 Cyclosporine 1 to 3 mg/kg/day controlled acute disease in six patients with moderate to severe pemphigus vulgaris uncontrolled with conventional therapies. Within 8 to 10 weeks after cyclosporine therapy was initiated, the lesions began to heal with no occurrence of new lesions noted.…”
Section: Pemphigus Vulgarismentioning
confidence: 99%
“…However, the combination of steroids with adjuvant drugs diminished steroid-associated morbidity. Olszewska et al 2 reported that among other immunosuppressants, cyclophosphamide at a dose of 1.1-1.5 mg/kg/day is an adjuvant drug of choice in the treatment of moderate-to-severe PV. 2 Furthermore, rituximab, a chimeric monoclonal antibody against CD20, has been proven to be of benefit in refractory cases, in which therapy with conventionally accepted modalities is either not efficacious or not possible because of adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Olszewska et al 2 reported that among other immunosuppressants, cyclophosphamide at a dose of 1.1-1.5 mg/kg/day is an adjuvant drug of choice in the treatment of moderate-to-severe PV. 2 Furthermore, rituximab, a chimeric monoclonal antibody against CD20, has been proven to be of benefit in refractory cases, in which therapy with conventionally accepted modalities is either not efficacious or not possible because of adverse effects. 3 Respiratory tract involvement in paraneoplastic pemphigus has been extensively studied, while there is a lack of data regarding pulmonary function in PV.…”
Section: Introductionmentioning
confidence: 99%